Facility Management in Private Finance Initiative project in UTHM Pagoh Campus - Rahmat, Norshahida; Mariah Awang,; Rahman, M.A.A (International Journal of Sustainable Construction Engineering and Technology, 2021)
Facility management (FM) in Private Finance Initiative (PFI) involved a long-time process and duration in improving the infrastructure and associating the facilities. FM will give a support role or service within an organisation that have been strategically integrated approach to operating, maintaining, improving, and adapting the buildings and supporting services in order to create natural environment. In a long-term relationship, facility management need to evolve to a higher strategic level in compliance with the organisation’s strategy. At the end of the process, it will achieve best value and performance on delivery of support services. In this research, direct observation has been done to analyze facility management provided in UTHM Pagoh Campus. Furthermore, the satisfaction level of building occupants also was investigated by using different measurement factors in a structured questionnaire to measure the effectiveness. Hence, the results concluded that the total overall satisfaction of users towards facility provided by private sector are mostly satisfied among building occupants. From the results obtained, outdoor area was ranked first out of eight measurement factors. An interview has been done in order to clarify the success of facility management. It can be summarized that all the facility supplied by private sector were meets Key Performance Indicators (KPIs), by meant it also need to improvise their services provision.